Virtual Screening of Flavonoid Compounds as Potential Antibiofilm Agents Targeting Glucosyltransferase - Kurniatin, Popi Asri; Putri, Fadhilah Eka; Purwanto, Ukhradiya Magharaniq Safira (Tropical Biopharmaca Research Center, IPB University, 2025)
Dental caries are caused by plaque formation resulting from biofilm accumulation on tooth surfaces. The bacterium Streptococcus mutans plays a crucial role in biofilm formation, partly through the production of glucosyltransferase, which catalyzes biofilm synthesis. Flavonoids are secondary metabolites commonly found in plants, known for diverse biological properties, including antibiofilm effects. This study aimed to screen the potential of flavonoid compounds as antibiofilm agents through inhibition of glucosyltransferase using an in-silico approach. A total of 87 flavonoid compounds obtained from the ZINC database were evaluated via molecular docking methods. Screening results based on binding free energy (ΔG) values, analyzed using the PyRX-Virtual Screening Tool, indicated that 36 compounds had potential to inhibit glucosyltransferase. Further molecular docking using AutoDock Vina identified nine compounds with ΔG values more favorable than the natural ligand of glucosyltransferase (maltose). Molecular interaction analysis using LigPlot+ and PyMOL revealed that taxifolin, gallocatechin, and sakuranetin interacted with three catalytic residues of the enzyme, whereas the remaining six compounds interacted with two catalytic residues. Liquiritigenin exhibited the lowest ΔG (-7.0 kcal/mol) and an inhibition constant (Ki) of 7.39 µM, indicating high affinity for glucosyltransferase. This compound formed two hydrogen bonds and four hydrophobic interactions, engaging two catalytic residues of the enzyme, Asn481 and Trp517. These findings highlight the potential of flavonoids as antibiofilm agents via glucosyltransferase inhibition. Further experimental validation through in vitro studies is necessary to confirm these in-silico findings.